Developing Senior Navy Leaders Requirements for Flag Officer Expertise Today and in the Future - Hanser, Lawrence M. (RAND Corporation, 2008)
Could U.S. Navy officers be better prepared to become flag officers? This study examines the kinds of expertise required for successful performance in Navy flag billets, and whether recent pools of officers possess this experience. The authors also examine Navy trends over the past decade to identify the types of expertise likely to become more important for Navy leaders in the future.